Performance of pacu juveniles fed diets supplemented with L-carnitine - Moro, Evandro Bilha [UNESP]; Gomes, Ricácio Luan Marques [UNESP]; Rodrigues, Mariana Lins; Sanchez, Milena Souza dos Santos; Bittencourt, Fabio; Signor, Altevir (FapUNIFESP (SciELO), 2020)
The objective of this work was to determine the effect of L-carnitine supplementation on the productive performance and physiology of juvenile pacu (Piaractus mesopotamicus). A total of 288 pacu, with an initial average weight of 9.62±0.74 g, were fed experimental diets supplemented with 400, 800, 1,200, 1,600, and 2,000 mg kg-1 L-carnitine and a control diet (without supplementation), for 128 days. The following were evaluated: growth performance; carcass centesimal composition; intestinal, muscle, and hepatic histomorphologies; and oxidative stress. The fish hepatosomatic and viscerosomatic fat indexes increased with the inclusion of L-carnitine in the diets. The evaluation of carcass centesimal composition showed that the diets supplemented with 2,000 mg kg-1 L-carnitine caused a reduction in protein content and an increase in that of ethereal extract. Intestinal histomorphology indicated changes in the villi with L-carnitine supplementation. Moreover, hepatic lipid peroxidation occurred with the inclusion of 2,000 mg kg-1 L-carnitine. The supplementation with L-carnitine in the diets of pacu juveniles does not influence the development of the fish until the rate of 1,600 mg kg-1. However, high carcass lipid levels, as well as an increase in the hepatosomatic and viscerosomatic fat indexes, are observed in fish fed diets containing 2,000 mg kg-1.
Keywords: animal nutrition; carcass composition; histomorphology; oxidative stress; Piaractus mesopotamicus